Determinants of foreign direct investment of OECD countries 1991-2001 - Gast, Michael; Justus Liebig University Giessen (My University, 2005)
Using a fixed-effects panel data approach, FDI flows of 22 OECD countries are explained by gravity equations over the period 1991-2001. It is distinguished between all available observations, Intra-EU25 observations only, and observations not belonging to the EU25 area in order to control for EU-specific effects. Regressions are repeated with exports as dependent variable in order to capture diverging influences for trade flows. Changes in total market size and relative market size are important factors that lead both FDI and exports in the same direction. However, relative market size is only significant in the FDI equation when variation between the EU25 area and other investment is taken into account, thus indicating a concentration of FDI within Western and Central Europe. Stock market booms boost FDI but not exports. Differences in significance levels/signs of coefficients of political indicators and exchange rate changes indicate that exports are demand-driven while FDI is supply-driven. Year dummies interacted with country distance show that, overall, FDI and exports tended to flow less to distant countries over the period under consideration. However, this trend is reversed for exports within the EU25 area.
Keywords: foreign direct investment and international trade; multinational firms; models with panel data; ddc:330